MEMBANGUN LITERASI DIGITAL YANG KUAT : KEBERDAYAAN MASYARAKAT DALAM MENCEGAH PENYEBARAN HOAKS - Ulum, Panji; Al Hidayat, Nanang; Sari, Mela; Esdhona, Ha; Tarjo; Mardansyah; Z, Zahlimar (Politeknik Negeri Sriwijaya, 2023)
This community engagement aims to discuss and implement strategies for building strong digital literacy to enhance community empowerment in tackling the spread of hoaxes. Through a series of activities such as counseling and training sessions digital literacy, we actively involve the community to improve their understanding of digital media, information verification, and hoax identification. The results show a significant increased in digital literacy skills and community awareness of invalid information. The program also provided a platform for collaboration between academics, practitioners, and the community to build a sustainable digital literacy ecosystem. In conclusion, this collaborative effort promotes community empowerment in combating the spread of hoaxes and strengthens collective defenses against misinformation.